Treatment of Radius Curvus in a Young Dog with Association of Radial Physeal Stapling, Ulnar Ostectomy and Transarticular Dynamic External Fixator Techniques - Simon, Fernanda; Muzzi, Leonardo Augusto Lopes; Pacheco, Larissa Teixeira; Muzzi, Ruthnea Aparecida Lázaro; Freitas, Laura Lourenço; Perez Neto, Daniel Munhoz Garcia; Abreu, Daniela Saldanha; Momesso, Eric Orlando Barbosa (Acta Scientiae Veterinariae, 2021)
Background: Radius curvus is a clinical manifestation of the premature closure of the distal ulnar physis and the most common physeal disease in dogs, representing 63% of all physeal injuries. There are few reports indicating the technique of stapling for treatment of radius curvus in squeletically immature dogs. The aim of this study is to report a case of radius curvus in a young dog successfully treated with a combination of 3 surgical tecniques: 1- Stapling the medial and cranial portions of the distal radial physis; 2- Oblique osteotomy of the proximal ulna and ostectomy of the distal ulna, and 3- Dynamic external skeletal fixation in the elbow joint. Case: A 5-month-old female dog was referred to the University Veterinary Hospital with a history of left thoracic limb deformity for 2 weeks. There was a history of possible traumatic event on the front limb, in addition to providing nutritional supplements daily. In the radiographic evaluation the changes were identified in the left thoracic limb: shortening of the ulna, procurvatum and medial angulation of the distal radius, increased joint space and articular incongruity of the elbow joint. The dog was subjected to surgical treatment by the combination of three main surgical techniques. For the stapling of the distal radial physis the surgical approach on the cranial-medial surface of the distal radius was made. Two surgical staples were positioned in the distal radial physis. Thereafter a caudal approach was made to the distal region of the ulnar diaphysis for the distal ostectomy of the ulna. A bone segment of 1 cm in length of the distal ulnar diaphysis was removed. Another caudal approach was made to the proximal region of the ulnar diaphysis and a proximal oblique osteotomy of the ulna was performed. For the dynamic external skeletal fixation in the elbow joint two Steinmann pins were inserted. The first pin was proximal to the supracondilar foramen of the humerus and the second pin was caudal to the trochlear notch of the ulna, both parallel to the joint surface. To create a dynamic system, the pin tips were connected with elastic rubber bands on the medial and lateral sides of the elbow joint. Clinical and radiographic revaluation were made at 15, 30 and 60 days after surgery. Total correction of the limb deviation was achieved at 60 days postoperative. Two years after the surgical procedure, the owner was contacted and reported that the dog was very well and with no change in the operated limb. Discussion: The most common cause of premature closure of the distal ulnar physis is trauma. Due to the proper conical shape of the distal ulnar physis, there is more predisposition to the compression of the germinative cells in traumatic events, leading to radius curvus disease. Another cause of the radius curvus is the nutritional disbalances. In the reported case the patient had both predisponent factors, although unilateral limb involvement suggested trauma with primary causative agent. The treatment included the interruption of the supplementation of the diet associated with surgical techniques. The stapling of the distal radial physis is usually indicated for mild angular valgus deviation. In the current case the technique was applied with success regardless of the higher grade of radial deviation. Generally, the ulnar ostectomy is preferred to the osteotomy, since it reduces the rate of ulnar osteosynthesis, ensuring that the restrictive effect of the ulna upon the radial growth does not restart. In the reported case the ulnar ostectomy was associated with ulnar osteotomy to achieve a more effective result. Furthermore, the proximal ulnar osteotomy is usually indicated when elbow subluxation is present. In the current case the joint congruence was improved with the use of the dynamic external skeletal fixator.